Perception of tutors and students about PBL conducted for PPSP and PPSG students - Barman, Arunodaya; Jaafar, Rogayah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Context: Problem-based learning is one of the teaching learning methods that gives students an opportunity to "learn to learn," by working in groups to seek solutions to real world problems. In spite of the growth and advantages of PBL, there is continuing debate about its effectiveness over the conventional teaching learning methods. In the School of Medical Sciences (SMS) and the School of Dental Sciences (SDS), Universiti Sains Malaysia (USM}, the MD and DDS programs are of 5 years duration. Basically the curriculum is problem-based and community oriented. Methods: Opinions and attitudes of tutors and students about PBL sessions conducted for the students of SMS and SDS were studied by a questionnaire survey. Results: Students enjoyed the sessions but they felt that tutors' guidance and contribution in the discussion might make the sessions a better success. They found the sessions are very helpful in acquiring communication and group interaction skills and in-depth understanding of the topics of study. These sessions helped them to relate basic sciences knowledge to the clinical sciences. They felt that use of repeated triggers is not in favour of the principles ofPBL. Most tutors have training to conduct the PBL sessions and they enjoy facilitating the sessions. They were in the opinion of that the content of the PBL sessions are related to the objectives of the block, attending PBL sessions help their students to link basic sciences to their clinical appraisal skills, students need to work harder to achieve certain learning objectives through PBL session than through lecture, students in the group did not participate in discussion as expected, time allotted for a PBLsession is enough, classrooms for PBL sessions are reasonably comfortable, learning resources are available to their students and they did not spend major part of their teaching time in PBL. Fifty percent of the respondents felt that the number of students in each group is appropriate to conduct the session. No relation was seen between the personal variables and any one of the opinions of the tutors. Discussion and Conclusion: PBL sessions conducted for the students of SMS and SDS is a successful teaching learning approach. Most tutors and students enjoyed the method. There are however some misconceptions about the method too. Tutors, SMS and SDS students should continue to be briefed on the philosophy, principles and objectives of the PBL as well as their roles in the session.